Creating a National Bibliographic Past: The Institute for Hebrew Bibliography - Kohn, Roger (Judaica Librarianship, 2007)
The mission of the Institute for Hebrew Bibliography (IHB), located at the Jewish and National University Library (JNUL) in Jerusalem from the early 1960s to the present, is to describe all of the books printed in Hebrew characters since the invention of printing to 1960. The ambitious scope of the project was set only after discussions between historians and catalogers. The IHB created two card catalogs, one for bibliographic descriptions, and a second for biographies of Hebrew authors. The release, in 1994, of The Bibliography of the Hebrew Book CD-ROM, followed in 2002 by an Internet-accessible database (updated in 2004), are benchmarks that allow the public to assess the work of the IHB. Technological advances can be used to deliver a clean and easily searchable database only when basic concepts of cataloging/database retrieval have been fully addressed.